Integrating ICT to Improve Students' Achievement in Thematic Learning Islamic Education in the Indonesian School in Bangkok - Nurul Qomariah; Budi Murtiyasa; Galih Albarra Shidiq (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2023)
This research aimed to identify how technology helped students develop their achievement by applying ICT-based learning media in thematic learning of Islamic Education at the Indonesian School in Bangkok. One of the important issues in elementary school is the need for more materials and resources for teaching and learning. Currently, technology is providing a better solution to solve the problem. In many cases, technology in education can improve students' knowledge and open their minds. This study used a qualitative method with a phenomenological approach of collecting data analysis consisting of interviews, documentation, and observation. The findings of this study explored the roles of students when they learned a technology by applying ICT-based learning media, which improves students’ motivation and inspire them to learn and provides a better understanding of learning in the classroom. However, these findings suggested that future studies could focus more on students' learning processes and teachers' abilities related to 21st-century skills.